Pembuatan Sistem Kendali Pelacak Surya Otomatis Pada PLTS - Harry Rudi Saragih; Yogie Rinaldy G; Adhy Prayitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Solar Electricity Generation (SEG) is an environmental freiandly technology takes advantage from phototovoltaic which is capable of converting solar energy to electricity energy. The Potensial of promoting SEG in Indonesia is very promizing in view of Indonesia's geographical location on the equator.The SEG with an automatic solar tracking system consist of LDR Sensor,Ardunio Uno, Servo Motor, Stepper Motor.Work operating procedur of the automatic solar tracking on SEG is begun from LDR sensor detection to solar position. Based upon LDR, data,Arduino (microcontroller)actived stepper motor to drive the photovoltaic panels to be always perpendicullar to the solar radiation during the operation. A such SEG system is considered able to give optimum energy output since the photovoltaic gets maximum radiant energy from the sun.The use of an automatic solar position control system on solar panels can increase panel performance and increase electrical power with an average output reaching almost 75% more than static solar panels.Keywords : SEG,Photovoltaic,Solar panels